1996
DOI: 10.1017/s1357729800014508
|View full text |Cite
|
Sign up to set email alerts
|

Milk production from grass silage diets: effects of high-protein concentrates for lactating heifers and cows on intake, milk production and milk nitrogen fractions

Abstract: To examine the effects of increasing the crude protein (CP) content of concentrates at either equal concentrate intake (increasing CP intake) or at reducing concentrate intake (equal CP intake), 44 multiparous HolsteinFriesian cows were allocated to one of five treatments for weeks 4 to 18 of lactation. The treatments were 6 kg dry matter (DM) per day of concentrates containing nominally 200, 300 or 400 g CP per kg DM or 9 or 3 kg DM per day of concentrates containing 200 or 600 g CP per kg DM respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
3
5
1
1
Order By: Relevance
“…MUN was increased as dietary CP increased. Similar increases in MUN have been observed in other studies (Baker et al, 1995;Colin-Schoellen et al, 2000;Sutton et al, 1996).…”
Section: Resultssupporting
confidence: 90%
“…MUN was increased as dietary CP increased. Similar increases in MUN have been observed in other studies (Baker et al, 1995;Colin-Schoellen et al, 2000;Sutton et al, 1996).…”
Section: Resultssupporting
confidence: 90%
“…Grass silage quality was quite typical according to Steen et al (1998) and MAFF (1992). The effect of the treatments on silage DMI was similar to the results of Sutton et al (1996) and Santos et al (1998). On a grass silage diet, Sutton et al (1996) increased the CP concentration (200, 300, and 400 g CP/ kg DM) in the concentrate using soybean meal and fish meal, and at equal concentrate intakes no significant effects on silage DMI were detected.…”
Section: Discussionsupporting
confidence: 72%
“…The effect of the treatments on silage DMI was similar to the results of Sutton et al (1996) and Santos et al (1998). On a grass silage diet, Sutton et al (1996) increased the CP concentration (200, 300, and 400 g CP/ kg DM) in the concentrate using soybean meal and fish meal, and at equal concentrate intakes no significant effects on silage DMI were detected. Similar results were observed by Santos et al (1998), who compared 15 trials with dairy cows supplemented with soybean meal vs treated soybean meal and concluded that total DMI was unaffected by increasing supplies of RUP.…”
Section: Discussionsupporting
confidence: 72%
“…Casein concentration in milk is closely related to the diet of the dairy cow and can be increased with increases in both dietary CP and energy (Sutton et al, 1996).…”
Section: Introductionmentioning
confidence: 99%